ANOVA APPLICATION TO ASSESS THE EFFECT OF TEMPERATURE ON VALUE AND YIELD ON LIQUID FUEL FROM HDPE - Nurull Fanani; Eky Novianarenti; Erlinda Ningsih; Kartika Udyani; Ari Prayitno; Denny Angga Saputra (Universitas Lambung Mangkurat, 2021)
Proper processing to overcome the abundance of plastic waste is needed. Currently, pyrolysis technology is one method that can overcome plastic waste. Pyrolysis is a thermochemical process, which breaks down long alkyl chains into hydrocarbons at high temperatures. This study aims to determine the effect of temperature on yield and heating value using the analysis of variance (ANOVA) method. The pyrolysis of plastic waste is carried out with HDPE plastic material. The pyrolysis process is carried out in a reactor with 50 grams of feed at various temperatures of 500, 550, 600 and 650⁰C. The conclusion that can be drawn from this research is that there is a decrease in yield and calorific value with increasing temperature. The results of the analysis concluded that temperature had an effect on the yield produced and the calorific value of the product. The best yield was obtained at 35.86% and a heating value of 10530.461cal / g at a temperature of 100oC. Based on the results of data analysis using the ANOVA method, it was found that the experimental hypothesis was that temperature had an effect on yield and calorific value.